The Condensation of Islam and Nusantara’s Culture - Moh Salapudin; Masykur Rozi; M. Fatihul Afham (JURNAL INDO-ISLAMIKA, 2021)
Islam in Nusantara has a unique character, which is the result of a long-term interaction process between religion and culture. Such condensation is crystallized in idea, conduct, and path. This article tries to elucidate the mixture process underwent in the light of cultural anthropology by relying on data contained in historical, social, and cultural sources. This study concludes that Islam-Nusantara condensation appeared in the form of politics, education, and culture, which is the result of the Islamization process. The manifestation of political condensation takes form in Islamic-Javanese kingship produced by Islamization efforts using power authority and Islamic theocracy. The appearance of educational condensation can be mirrored in santri community with its orthopraxy trend brought about by the enlightenment of ‘ulemas with their stronger religious orientation. The last is the cultural condensation identified in kejawen society which is caused by the syncretic approach of Islamization that combines Islamic Sufism and Javanese mysticism.